EFFECTIVENESS OF MANUAL THERAPY, PHYSICAL THERAPY IN CONJUNCTION WITH PATIENT EDUCATION FOR TEMPOROMANDIBULAR DISORDERS: A RANDOMIZED CONTROLLED STUDY. - Saeed Ullah Shah,; Sana Shakil Khan,; Sadia Moin,; Shumaila Younus,; Hina Jabeen,; Kanwal safeer, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Temporomandibular joint (TMJ) disorders represent a significant health concern affecting a substantial portion of the population worldwide. The management of TMJ disorders often involves a multifaceted approach including physiotherapy techniques, manual exercise interventions, patient education, and medication therapy. Objective: The purpose of this research is to examine the Effectiveness of manual therapy, and physical therapy in conjunction with patient education for temporomandibular disorders. Methods: 40 patients with TMDS were randomized into two groups: one for home physical therapy and the other for manual therapy plus physical therapy. Patient education and counseling were done in both groups. the patient had assessments both before and after. Results: The study made a comparison of two groups: one received physical therapy only (n=20) and the other group received a combination of physical and manual therapy (n=20). There were no significant differences between the two groups in terms of age, gender distribution, or the affected side of the face (p>0.05). Conclusion: For TMJ issues, physical therapy patient education is a useful therapeutic method. Moreover, combining these modalities with manual therapy improves results beyond what would be achieved with just these modalities alone.